1997
DOI: 10.1046/j.1471-4159.1997.68052119.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inactivation of Postsynaptic Density‐Associated and Soluble Ca2+/Calmodulin‐Dependent Protein Kinase II by Protein Phosphatases 1 and 2A

Abstract: Autophosphorylation of Ca2/calmodulin-dependent protein kinase II (CaMKII) at Thr286 generates Ca2~-independent activity. As an initial step toward understanding CaMKII inactivation, protein phosphatase classes (PP1, PP2A, PP2B, or PP2C) responsible for dephosphorylation of Thr286 in rat forebrain subcellular fractions were identified using phosphatase inhibitors/activators, by fractionation using ion exchange chromatography and by immunoblotting. PP2A-like enzymes account for >70% of activity toward exogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
207
3
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 285 publications
(224 citation statements)
references
References 39 publications
(51 reference statements)
7
207
3
2
Order By: Relevance
“…This scenario would still be interesting, because it suggests that αCaMKII that is at the PSD is kept in a preferentially inactivated state under basal conditions. A possible mechanism for this is differential control by phosphatases at the post-synaptic density compared to elsewhere in the neuron, and indeed it has been demonstrated that T286 is dephosphorylated by different phosphatases depending on if the kinase is PSD-associated or soluble (Strack et al, 1997a). Whatever the explanation of these results, it is clear that our data are incompatible with a model in which T286 phosphorylated αCaMKII is preferentially localized to the PSD and T305 phosphorylated αCaMKII is excluded from the PSD.…”
Section: Discussioncontrasting
confidence: 80%
“…This scenario would still be interesting, because it suggests that αCaMKII that is at the PSD is kept in a preferentially inactivated state under basal conditions. A possible mechanism for this is differential control by phosphatases at the post-synaptic density compared to elsewhere in the neuron, and indeed it has been demonstrated that T286 is dephosphorylated by different phosphatases depending on if the kinase is PSD-associated or soluble (Strack et al, 1997a). Whatever the explanation of these results, it is clear that our data are incompatible with a model in which T286 phosphorylated αCaMKII is preferentially localized to the PSD and T305 phosphorylated αCaMKII is excluded from the PSD.…”
Section: Discussioncontrasting
confidence: 80%
“…It should be noted, however, that, when autophosphorylated on a critical threonine residue, the CaMKII has 1000-fold increased affinity for Ca 2 þ /calmodulin and is active even in the absence of Ca 2 þ /calmodulin (for recent reviews, see Colbran 13 and Hudmon and Schulman 34 ). Since phosphoprotein phosphatase type 2A (PP2A) and phosphoprotein phosphatase type 1 (PP1) catalyze the dephosphorylation of autoactivated CaMKII, 13,35 an obvious pathway for PPinhibitor activation of CaMKII is by blocking its dephosphorylation, 33 thereby circumventing the need for increased Ca i 2 þ . Recently, Howe et al 36 have shown that reactive oxygen radicals can inactivate PP2A and thereby stimulate CaMKII.…”
Section: Discussionmentioning
confidence: 99%
“…To determine protein synthesis activity, the detached cells were centrifuged (400 Â g, 2 min), resuspended in fresh medium containing [ 35 The incubation was terminated by the addition of ice-cold 7% aqueous trichloroacetic acid. The cell precipitates were transferred to tubes, centrifuged (15 000 Â g, 15 min), and the pellet washed three times in 5% trichloroacetic acid and twice in diethyl ether, before dissolving in SDS loading buffer (50 mM Tris-HCl, pH 6.8, 10% glycerol, 2% SDS, 100 mM DTT and 0.05% bromophenol blue).…”
Section: Apoptotic Cell Deathmentioning
confidence: 99%
“…Immunopurification, Western Blot, and Gel Analysis-The general serine/threonine phosphatase antibody (FL-18) was from Santa Cruz Biotechnology. Antibodies to OGT, PP1␣, PP1␤, PP1␥, PP4, and PP6 have been described previously (12,(22)(23)(24)(25)(26)(27). Negative controls used normal rabbit IgG.…”
Section: Methodsmentioning
confidence: 99%